Модель эколого-генетического контроля биосинтеза тимола в эфирном масле Thymus L. - КОРСАКОВА, СВЕТЛАНА ПАВЛОВНА; РАБОТЯГОВ, ВАЛЕРИЙ ДМИТРИЕВИЧ; ВИНОГРАДОВ, БОРИС АЛЕКСЕЕВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Модель эколого-генетического контроля биосинтеза тимола в эфирном масле Thymus L.